Strengthening of Al0.15CoCrCuFeNiTix-C (x=0, 1, 2) high-entropy alloys by grain refinement and using nanoscale carbides via powder metallurgical route - Nam, Seungjin; Kim, Moon J.; Hwang, Jun Yeon; Choi, Hyunjoo (ELSEVIER SCIENCE SA, 2018)
In this study, Al0.15CoCrCuFeNiTix-C (x = 0, 1, 2) high-entropy alloys (HEAs) were produced via powder metallurgy routes, and the microstructural evolution and mechanical properties of the alloys were investigated with respect to the alloys of Ti content. Cr-carbides were formed in the Ti-free alloy, whereas the Ti-containing alloys contained Ti-carbides instead of Cr-carbides because Ti has a higher affinity for C than it does for Cr. Sigma phases were also formed in the Al0.15CoCrCuFeNiTi2-C alloy. The formation of carbides and intermetallic compounds altered the composition and structure of the solid-solution phases. High-energy ball-milling led to the refinement of microstructures to the nanoscale, and the average grain size of the alloys decreased with increasing Ti content because of the grain-boundary pinning effect of TiC. As a result, the Al0.15CoCrCuFeNiTix-C (x = 0, 1, 2) alloys exhibited high strengths of 2047, 2199, and 2877 MPa, respectively. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: MECHANICAL-PROPERTIES; PHASE-FORMATION; COMPRESSIVE PROPERTIES; STRUCTURAL EVOLUTION; TENSILE PROPERTIES; THERMAL-STABILITY; WEAR-RESISTANCE; SOLID-SOLUTION; MICROSTRUCTURE; BEHAVIOR